The Internet Based Resources for Virtual Listening Skills Teaching and Learning in Ban Raisooksan School, Loei Province, Thailand - Arti, Usfah Vindy (Journal of English Teaching, Literature, and Applied Linguistics, 2021)
The purpose of this study is describing the use of internet based resources method in teaching English listening skills for primary school students in Ban Raisooksan School, Loei, Thailand. In this research the researcher describes the activities of teaching English listening skills by using internet based resources method. The data resources are from teacher and students in Ban Raisooksan School, Loei, Thailand. The students are from 5th grade (P5 students) and the total of the students are 8 students. The data were collected through observation and semi-structured interviews between teacher and students. The researcher go through six weekly listening activities using Internet based resources and assignments. Based on the study, this paper concludes that the use of internet based resources method would significantly improve the virtual teaching and learning. Through writing this article, the author hopes to improve the awareness of the internet based resources method by the teachers. The teachers will use the internet based resources method to carry on teaching in the classroom and help the students learn virtually.